SZ_GERICHTE STK 2019 58 vom 25. August 2020 , BetmG, SVG, Pornografie, Landesverweisung und Einziehung - SZ Gerichte (2020)
BetmG, SVG, Pornografie, Landesverweisung und Einziehung | Betäubungsmittelgesetz